Wartość rodzin dzieci z niepełnosprawnością - Jasnos, Andrzej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The family is a community of people, which is the basic form of individual and social life. It is a natural and irreplaceable environment in which every person can develop integrally according to their capabilities. Nowadays, there are numerous changes taking place in the life of societies, as well as individual human beings. Universal relativism, and through strongly ideologized environments, the questioning of fundamental values ​​has its repercussions in the perception and implementation of family life. The most prominent examples are the numerous forms of pressure and the attempt to change the definition of marriage as a union of man and woman, as well as questioning the basic right to life from conception to natural death. Poland in recent years in Europe has become a kind of island carrying and preserving the tradition of basic values, including families. The process of creating a family is not an easy task, especially in post-modern culture. An even more difficult task is to be fulfilled in the families struggling with the child’s disability. Therefore, this reflection aims to outline the situation of families with children with disabilities, emphasizing values.